2013
DOI: 10.1111/adb.12025
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol affects acylated and total ghrelin levels in peripheral blood of alcohol-dependent rats

Abstract: There is a hypothesis that ghrelin could take part in the central effects of alcohol as well as function as a peripheral indicator of the changes which occur during long-term alcohol consumption. The aim of this study was to determine a correlation between alcohol concentration and acylated and total form of ghrelin after a single administration of alcohol (intraperitoneal, i.p.) (experiment 1) and prolonged ethanol consumption (experiment 2). The study was performed using Wistar alcohol preferring (PR) and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 52 publications
3
16
0
Order By: Relevance
“…Therefore, searching for a new substances that might affect development of tolerance seems to be justified. The aim of our study was to examine the influence of Sal, the active compound of R. rosea, on the development of alcohol tolerance in rats according to model proposed by Crabbe [25], subsequently successfully applied in our team [26]. Development of tolerance to ethanol can be evaluated on changes in the hypothermic and sedative action of ethanol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, searching for a new substances that might affect development of tolerance seems to be justified. The aim of our study was to examine the influence of Sal, the active compound of R. rosea, on the development of alcohol tolerance in rats according to model proposed by Crabbe [25], subsequently successfully applied in our team [26]. Development of tolerance to ethanol can be evaluated on changes in the hypothermic and sedative action of ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…Sampling was performed with Perkin Elmer AutoSystem XL GC with Headspace Sampler Turbomatrix 40, equipped with two capillary columns Elite BAC-1, BAC-2 (Perkin Elmer, length: 30 m, diameter: 0.32 mm, film thickness: 1.8 μm, software: Totalchrom Workstation ver. 6.2.0) [26].…”
Section: Measurement Of Ethanol Concentration In Bloodmentioning
confidence: 99%
“…However, another study showed that 10 months of alcohol consumption decreased GHS-R1a expression in the VTA of rats (Suchankova et al, 2013). P rats and WHP rats showed greater reductions in plasma acyl-ghrelin levels after alcohol consumption relative to NP and WLP rats (Szulc et al, 2013). Together these studies imply that alcohol affects circulating ghrelin and central ghrelin signaling.…”
Section: Ghrelinmentioning
confidence: 99%
“…; Szulc et al . ). Furthermore, central and intra‐VTA administration of ghrelin increased alcohol intake in mice (Jerlhag et al .…”
mentioning
confidence: 99%